Analisis Keefektifan Media Flash Card pada Siswa dalam Menulis Teks Recount - Afore Tahir Harefa; Kristof Martin E Telaumbanua (Neolectura, 2022)
Writing is to express idea, feeling and argument meaningfully into the form of words to sentences with some structurally compositions. This research based on the researcher’s observation in the classroom of English teaching and learning at Senior High School, which had experienced in ineffectiveness. This study aims to obtain information or an overview of the effectiveness of learning both in terms of student enthusiasm and the learning media used by the teacher. The research designed in qualitative research methods. The population of this study was the students of X-MIPA-1, amounting to 36 students. Data were collected through observation sheet, test and interview. The result of the observation sheet about students’ enthusiasm in the first observation was 52.59%, while the results of the observation sheet about the enthusiasm of students in the second observation were 81.90%. Likewise, the result of the test carried out before the application of the learning media were 63.88%, while the result of the test carried out after the application of the learning media were 88.22%. This is also influenced by the result of the observation sheet about the learning media applied by the teacher were 75%. It can be concluded that the application of learning media can increase the effectiveness of learning. The suggestion recommended the flashcard to students in learning recount text, flashcard contributed to the students’ active and participation, flashcard increased the creativities of English classroom, with many modification applied in the classroom.